Harry Potter and the sorcerer's stone [compact disc, unabridged] - Rowling, J. K. (Rowling, J. K. Year ... at Hogwarts, 1999)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts School for Wizards and Witches.